Use of Wavelets in Electrocardiogram Research: a Literature Review - Darwan Darwan; Hindayati Mustafidah (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2021)
Currently the introduction and detection of heart abnormalities using electrocardiogram (ECG) is very much. ECG conducted many research approaches in various methods, one of which is wavelet. This article aims to explain the trends of ECG research using wavelet approach in the last ten years. We reviewed journals with the keyword title